DIGITALIZATION ENTREPRENEURSHIP AND SMALL BUSINESS ASSESSMENT OF THE IMPACT ON DEVELOPMENT - Tulagan Tukhtaraliev (Antis Publisher, 2024)
this article analyzes the state of development of small business and private entrepreneurship, its share in macroeconomic indicators such as GDP, exports and industry. Also, proposals for the main ways of developing small business and private entrepreneurship were previously asked.The impact of digitalization, measured by the share of Internet users, on the share of entrepreneurship and small businesses, was analyzed using the smallest squares usluli in the AOS of data from the World Bank and the statistical agency under the president of the Republic of Uzbekistan. From the results of the Model, it can be seen that there is a correct correlation between the increase in the share of internet users and the share of small business and private entrepreneurship